Study the Effect of Quercus infectoria Galls Extracts on Growth of Candida albicans and Candida glabrata In Vitro Which Isolated from Vaginal Swabs - Hassan, Heba Fadel (The Iraqi Journal of Veterinary Medicine, 2011)
The results of isolation in this research showed prevalence of Candida albicans at 35.7% which isolated from 70 samples of infected women who suffered from vaginal thrush compared with other infected agent. In vitro antifungal activities of ethanolic and aqueous( hot and cold distilled water) extracts of Quercus infectoria galls were tested against growth of C. albicans and C.glabrata in different concentration , showed that ethanolic extracts of Quercus infectoria was more effective against C. albicans at concentration 700mg/ml while the aqueous( hot and cold distilled water) extracts were more effective against C.glabrata compared with growth of C. albicans at same extracts .